2003
DOI: 10.1079/ber2003237
|View full text |Cite
|
Sign up to set email alerts
|

Diving beetles (Dytiscidae) as predators of mosquito larvae (Culicidae) in field experiments and in laboratory tests of prey preference

Abstract: Field experiments were performed in artificial ponds to evaluate how the density of predatory diving beetles (Dytiscidae) would affect the population levels of mosquito larvae (Culicidae). Mosquitoes colonizing the ponds were predominantly species of the genus Culex. In 2000, most of the dytiscids colonizing the ponds were small (Hydroporus spp.), and these predators had no impact on the size of larval mosquito populations, not even in ponds with added dytiscids. In 2001, larger beetles (Ilybius, Rhantus, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 18 publications
2
64
1
3
Order By: Relevance
“…Dytiscids and some aquatic Hemiptera as generalist predators have been claimed as predators on mosquito larvae (Nilsson & Svensson, 1994;Blaustein, 1998;Lundkvist et al, 2003;Medlock & Snow, 2008), but no direct Bti-effect is known on these orders (Boisvert & Boisvert, 2000). In our analyses, Bti against mosquito larvae seemed to play only a minor role in structuring the dytiscid species assemblage, and the only significant result was a possible positive effect on the medium-sized dytiscids.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Dytiscids and some aquatic Hemiptera as generalist predators have been claimed as predators on mosquito larvae (Nilsson & Svensson, 1994;Blaustein, 1998;Lundkvist et al, 2003;Medlock & Snow, 2008), but no direct Bti-effect is known on these orders (Boisvert & Boisvert, 2000). In our analyses, Bti against mosquito larvae seemed to play only a minor role in structuring the dytiscid species assemblage, and the only significant result was a possible positive effect on the medium-sized dytiscids.…”
Section: Discussionmentioning
confidence: 60%
“…In fact, Deding (1988) found Chironomidae and small crustaceans to dominate as recognizable food items for the majority of the dytiscid species studied. Lundkvist et al (2003) found different prey preference of three medium-sized dytiscid species on two alternative preys (mosquito larvae and Daphnia) in laboratory tests. Flood water mosquito larvae may constitute an example of an unpredictable super-abundant food resource that varies strongly within and between years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations